Information‐sharing between healthcare professionals, parents and children with cancer: more than a matter of information exchange. (4th November 2015) - Coyne, I.; Amory, A.; Gibson, F.; Kiernan, G.
Abstract : This study examined participants' views on children's participation in information‐sharing and communication interactions. A descriptive qualitative approach was taken with individual interviews held with children (The term 'children' is used to denote both children and adolescents and to avoid cumbersome repetition.) aged 7–16 years ( n = 20), their parents ( n = 22) and healthcare professionals ( n = 40) at a children's hospital in Ireland. Data were analysed using the constant comparative method and managed with NVivo (version 8). The findings indicate that professionals strongly supported an open and honest approach to information‐sharing; however, this viewpoint was not shared by all parents. The need to maintain hope and spirit and promote an optimistic identity influenced the amount and type of information shared by parents. Children trusted their parents to share information, and valued their parents' role as interpreters of information, advocates, and communication buffers. Most professionals endorsed parents' primacy as managers of information but experienced difficulty navigating a restricted stance. This study adds important insights into the complexities of information‐sharing in triadic encounters. Professionals need to maintain an open mind about information‐sharing strategies families may choose, remain sensitive to parents and children's information requirements and adopt a flexible approach to information provision.